PREGNANCY OUTCOME OF GESTATIONAL DIABETIC MOTHERS: EXPERIENCE IN A TERTIARY CENTER - Al-Hakeem, Malak M. (Medknow Publications & Media Pvt Ltd, 2006)
BACKGROUND: Carbohydrate intolerance is the most common metabolic complication of pregnancy. Gestational Diabetes Mellitus (GDM) poses numerous problems for both mother and fetus. The objectives of this study are to find out the incidence of gestational diabetes mellitus in pregnant women and their pregnancy outcomes. It was also to discover the risk factors for the admission of neonates to the Neonatal Intensive Care Unit (NICU). DESIGN AND PATIENTS: A hospital-based prospective study performed at King Khalid University hospital (KKUH), where 685 pregnant women who were diagnosed with gestational diabetes mellitus, out of 8000 pregnant women registered between January 2000 - December 2001, were followed and their outcomes studied. RESULTS: The incidence of gestational diabetes mellitus was found to be 8.6% (95% C.I: 8.1, 9.3). There were 511 (74.6%) spontaneous vertex deliveries, and 148 (21.6%) were delivered by lower segment cesarean section. Maternal morbidity in these women was 1.2%. A total of 697 babies were delivered by these 685 women, out of whom 675 were singleton pregnancies, 9 sets of twins and one set of quadruplets. Six-hundred-eighty-seven babies were born alive, 7 babies died in utero and 3 died in the neonatal period. The incidence of neonatal intensive care admission was 4.9%. The mean length of stay in the NICU was 16 days. The commonest cause of neonatal NICU admission was hyperbilirubinemia (41.2%). The risk factors for NICU admission were delivery by non SVD procedure (RR: 4.6, 95% C.I:2.8, 7.7), preterm deliveries, (RR: 4.6, 95% C.I.:2.7, 7.7), and induction of labor (RR: 2.5, 95% C.I: 1.4, 4.5). CONCLUSION: The observation and quantification of maternal outcomes with gestational diabetes mellitus are necessary, so that proper measures could be taken to reduce complications during delivery and the neonatal period and thereby, minimize particularly NICU admission rate.